The anisotropic properties and Debye temperatures of Ti-Zn compounds: a first-principles calculation. (2nd October 2019) - Yan, Juan; Shou, Hongwei; Peng, Mingjun; Duan, Yonghua; Cao, Yong
Abstract: In this work, the first-principles calculations based on density functional theory (DFT) was used to investigate the single and polycrystalline elastic properties, anisotropies of bulk and Young's moduli, Debye temperatures and acoustic velocities of Ti2 Zn, TiZn, TiZn2 and TiZn3 . The calculated results illustrate that TiZn2 has the largest hardness. Besides, from Debye temperature, it indicates that TiZn2 has the strongest bonding strength. The nature of TiZn2 is ductile and others are brittle. And Ti2 Zn is the brittlest. According to the three-dimension surface constructions and projections of bulk and Young's moduli, it is obviously seen that the most anisotropic phase is TiZn. The order of anisotropy is TiZn (cubic) > Ti2 Zn > TiZn3  > TiZn2 . However, in many binary systems, the intermetallic with a cubic structure is always isotropic. It is an interesting discovery.